The regulation of the freedom of speech on the internet: inter-american standards and the facebook case - Cabrera Sánchez, Alexandra (2017)
In the following lines the  author  analyzes the right to freedom of speech, based on the historical and conceptual framework to analyze the limits and Inter-American development of this right in order to analyze its dissemination through internet taking advantage of regulatory guidelines of this right American System and intermediary companies. Finally, it analyzes gaps focusing on the absence of the State and its obligations to respect and guarantee by allowing ample affectation of fundamental rights through the network.